Desiccation tolerance in the resurrection plant Barbacenia graminifolia involves changes in redox metabolism and carotenoid oxidation - Vieira, Evandro Alves; Gaspar, Marilia; Caldeira, Cecílio Frois; Munné-Bosch, Sergi; Braga, Marcia Regina (Frontiers in Plant Science, 2024)
Desiccation tolerance in vegetative tissues enables resurrection plants to remain quiescent under severe drought and rapidly recover full metabolism once water becomes available. Barbacenia graminifolia is a resurrection plant that occurs at high altitudes, typically growing on rock slits, exposed to high irradiance and limited water availability. We analyzed the levels of reactive oxygen species (ROS) and antioxidants, carotenoids and its cleavage products, and stressrelated phytohormones in fully hydrated, dehydrated, and rehydrated leaves of B. graminifolia. This species exhibited a precise adjustment of its antioxidant metabolism to desiccation. Our results indicate that this adjustment is associated with enhanced carotenoid and apocarotenoids, α-tocopherol and compounds of ascorbate-glutathione cycle. While α-carotene and lutein increased in driedleaves suggesting effective protection of the light-harvesting complexes, the decrease in β-carotene was accompanied of 10.2-fold increase in the content of β-cyclocitral, an apocarotenoid implicated in the regulation of abiotic stresses, compared to hydrated plants. The principal component analysis showed that dehydrated plants at 30 days formed a separate cluster from both hydrated and dehydrated plants for up to 15 days. This regulation might be part of the protective metabolic strategies employed by this resurrection plant to survive water scarcity in its inhospitable habitat.